Cytology and immunocytochemistry of bilateral breast metastases from prostatic cancer. Report of a case - Schmitt, F. C.; Tani, E.; Skoog, L. (My University, 1989)
The cytologic findings in fine needle aspirates of a previously treated prostatic cancer metastatic to both breasts in a 65-year-old man are described. The prostatic origin of the poorly differentiated adenocarcinoma cells was demonstrated by identification of cytoplasmic prostate-specific antigen. The clinical importance of a conclusive diagnosis differentiating a primary from a metastatic lesion is discussed; this case illustrates the value of immunocytochemical analysis as an aid to cytomorphologic diagnosis in making such determinations.